2022
DOI: 10.1177/19714009221126015
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric-type diffuse low-grade glioma with MYB/MYBL1 alteration: report of 2 cases

Abstract: 2016 World Health Organization (WHO) Classification of Tumors of the Central Nervous System (CNS) has shown how molecular features can impact the classification of brain tumors. The continued combination of molecular features with histopathology has led to distinguish tumors with similar histopathologic features but distinct clinical prognosis. The 2021 revised 5. edition of the WHO classification further includes molecular features for CNS tumor categorization including MYB/MYBL1 altered diffuse astrocytoma w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A prior report by Johnson et al 8 mentioned a false-positive T2-FLAIR mismatch sign in the following: 1) a pilomyxoid astrocytoma in a 2-year-old child, 2) a non-neoplastic lesion (heterotopic gray matter) in a 12-year-old child, 3) a H3K27M-mutant midline glioma in a 14year-old adolescent, and 4) a low-grade astrocytoma harboring MYB rearrangement in an 18-year-old individual. In addition, Kalelioglu et al 12 reported the T2-FLAIR mismatch sign in 1 of 2 pediatric-type diffuse low-grade gliomas with a MYB/MYBL1 alteration. In our cohort of 352 pLGGs, we found 25 tumors with a T2-FLAIR mismatch (7.1%).…”
Section: Discussionmentioning
confidence: 99%
“…A prior report by Johnson et al 8 mentioned a false-positive T2-FLAIR mismatch sign in the following: 1) a pilomyxoid astrocytoma in a 2-year-old child, 2) a non-neoplastic lesion (heterotopic gray matter) in a 12-year-old child, 3) a H3K27M-mutant midline glioma in a 14year-old adolescent, and 4) a low-grade astrocytoma harboring MYB rearrangement in an 18-year-old individual. In addition, Kalelioglu et al 12 reported the T2-FLAIR mismatch sign in 1 of 2 pediatric-type diffuse low-grade gliomas with a MYB/MYBL1 alteration. In our cohort of 352 pLGGs, we found 25 tumors with a T2-FLAIR mismatch (7.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The imaging findings have been rarely reported. Reports show that diffuse astrocytoma, MYB‐ or MYBL1 ‐altered is relatively well‐defined nonenhancing tumor, with mixed or hyperintensity on T2‐weighted image and does not show restricted diffusion 43,47 . A representative case is shown in Fig.…”
Section: Specific Molecular and Imaging Featuresmentioning
confidence: 99%
“…The tumor belongs to the family of MYB/MYBL1-altered gliomas and is an IDH -wild type. It exhibits low-grade histopathologic features and represents a distinct group of tumors with indolent behavior and a favorable prognosis ( 9 ). The tumor cell proliferation index is low and usually classified as WHO grade 1 ( 13 ).…”
Section: Characteristics Of Pdlggs Of Different Tumor Typesmentioning
confidence: 99%
“…Chiang et al ( 17 ) found that the 10-year progression-free survival and overall survival rates were 89.6% and 95.2%, respectively. The conservative approach is recommended for inert IDH-wild-type diffuse astrocytoma owing to its more favorable prognosis and progression-free survival ( 9 ). Yang et al ( 20 ) found that children with MYB amplification have a better prognosis and longer progression-free survival than those without MYB amplification.…”
Section: Characteristics Of Pdlggs Of Different Tumor Typesmentioning
confidence: 99%